SUICIDES IN POLAND AS A SOCIAL PROBLEM AND SOCIAL PHENOMENON - Kola, Anna Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
According to police statistics in 2013 in Poland there has been a sharp increase in the number of suicides among men, compared to previous years and to the number of suicides among women. Unfortunately, this trend continues to grow each year. Hence the idea of the article is to present problem and to shed some light on the phenomenon and try to characterise it, referencing the statistics and academic studies of suicides.